Identification of Potential miRNA-mRNA Regulatory Network Contributing to Hypertrophic Cardiomyopathy (HCM) - Wang, Lin; Lu, Fengmin; Xu, Jing (Frontiers in Cardiovascular Medicine, 2021)
Background: Hypertrophic cardiomyopathy (HCM) is a myocardial disease with unidentified pathogenesis. Increasing evidence indicated potential roles of microRNA(miRNA)-mRNA regulatory network in disease development. This study aimed to explore miRNA-mRNA axis in HCM. Methods: The miRNA and mRNA expression profiles obtained from the Gene Expression Omnibus (GEO) database were used to identify differentially expressed miRNAs (DEMs) and genes (DEGs) between hypertrophic cardiomyopathy (HCM) and normal samples. Target genes of DEMs were determined by miRTarBase. Gene ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were conducted to identify biological functions of the DEGs and DEMs. miRNA-mRNA regulatory network was constructed to identify the hub genes and miRNAs. Logistic regression model for HCM prediction was established basing on the network. Results: A total of 224 upregulated and 366 downregulated DEGs, 10 upregulated and 14 downregulated DEMs were determined. We identified 384 DEM-targeted genes, in which 20 were overlapped with the DEGs. The enriched pathological functions include extracellular structure organization, organ growth, phagosome and melanoma pathways. 4 miRNAs and 3 mRNAs, including hsa-miR-373, hsa-miR-371-3p, hsa-miR-34b, hsa-miR-452, ARHGDIA, SEC61A1 and MYC, were identified through miRNA-mRNA regulatory netowrk to construct logistic models. The area under curve (AUC) values over 0.9 suggested the good performance of the model. Conclusion: The potential miRNA-mRNA regulatory network and established logistic model in our study may provide promising diagnostic methods for HCM.